The willingness and attitudes of speech-language pathologists towards the use of mobile health technology: a survey study - Soheila Saeedi; Marjan Ghazisaeedi; Maryam Ebrahimi; Mohammad-Sadegh Seifpanahi; Hamid Bouraghi (BMC, 2023)
Abstract Background Mobile health (mHealth) technology could be used in different ways to treat various speech and language disorders. The attitude of speech-language pathologists (SLPs) towards this technology and their willingness to use it can play a significant role in the success of the therapies they provide. This study was conducted to investigate the willingness and attitude of SLPs towards the use of mHealth technology. Methods This cross-sectional study was conducted from September 2021 to April 2022 in Iran. A researcher-made questionnaire consisting of three parts (information related to demographic variables, attitude and willingness) was designed based on the past studies, and then given to all SLPs throughout Iran. Data were analyzed by SPSS software, using descriptive and inferential statistics (frequency, mean, Fisher's exact test, and analysis of variance). Also, the SLPs' willingness to use the desired technology was interpreted as a percentage as follows: 0-20% = not at all willing, 21-40% = slightly willing, 41-60% = moderately willing, 61-80% = highly willing, and above 80% = extremely willing. Results One hundred sixty speech-language pathologists from all over Iran participated in this study. The results showed that the willingness of 65.25% of SLPs to use the mentioned technology was at a good level, and according to the mentioned category, they had a high willingness to use this technology. In regard to the attitude of SLPs, the findings showed that SLPs believed that patients receive a higher quality of care during in-person visits than through mHealth technology. Also, this survey showed that SLPs were more inclined to use this technology to answer patients' questions. Non-payment of services provided through mHealth technology and privacy concerns were the reasons for the lack of use of this technology by SLPs. Conclusions SLPs are willing to use mHealth technology after solving the related challenges, including payment of costs and privacy concerns. However, SLPs believed that this technology will not be a suitable alternative to face-to-face sessions.